Knowledge, attitude and practice of islamic moral and ethics among students of selected modern arabic schools in Ibadan (2024)
Islamic moral and ethics are enunciated through revelations which comprise the Qur’an and the authentic teachings of the Prophet. Although studies reveal Islamic moral and ethics in the society, little research is available on the impact of Islamic moral and ethics among students of Arabic schools in Ibadan. Therefore, the study evaluates the knowledge, attitude and practice of Islamic moral and ethics among the students of selected modern Arabic schools in Ibadan. This qualitative and quantitative study explores the knowledge of Islamic moral and ethics as well as the students’ attitude and practice accordingly, using face-to- face in-depth interview with 200 students and 500 copies of questionnaire administered. Data collected through interview were thematically analysed and descriptive analysis was done for the questionnaires using Statistical Package for Social Science (SPSS). Findings of this study showed the knowledge and understanding of the concepts of moral and ethical behaviours in the Qur’an and the Sunnah among the students. It established the attitude of Islamic moral and ethical behaviour among them and recorded negative practices of the knowledge and attitude. Study findings suggest the adoption of unified and upgraded texts for Arabic schools on moral and ethics to cater for 21st century challenges. The study recommends appreciation of academic excellence as well as moral uprightness to encourage students on morality in their immediate community